2017
DOI: 10.21147/j.issn.1000-9604.2017.06.10
|View full text |Cite
|
Sign up to set email alerts
|

Survival difference between EGFR Del19 and L858R mutant advanced non-small cell lung cancer patients receiving gefitinib: a propensity score matching analysis

Abstract: No significant difference was found in the PFS or OS between the Del19 and L858R mutant NSCLC patients receiving gefitinib. The age gap might contribute to the survival differences between Del19 and L858R groups. PSM is of important value to the elimination of potential bias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
1
9
1
Order By: Relevance
“…As expected, both survival indices were better for patients with T790M-mediated resistance, reflecting the slow-growing nature of T790M-positive lung cancer (Figure 5, C and D ). In multivariate Cox analysis (Supplemental Figures 2 and 3), the poor prognostic factors, which had statistically significant effects on OS, were male sex [HR = 1.65, 95% CI 1.07-2.56, P = .03] and stage IVb [HR = 3.02, 95% CI 1.47-6.24, P < .01], whereas the types of EGFR mutation did not affect survival (Figure 5 and Supplemental Figure 3), which was also observed in another recent study using propensity score matching [25].…”
Section: Discussionsupporting
confidence: 73%
“…As expected, both survival indices were better for patients with T790M-mediated resistance, reflecting the slow-growing nature of T790M-positive lung cancer (Figure 5, C and D ). In multivariate Cox analysis (Supplemental Figures 2 and 3), the poor prognostic factors, which had statistically significant effects on OS, were male sex [HR = 1.65, 95% CI 1.07-2.56, P = .03] and stage IVb [HR = 3.02, 95% CI 1.47-6.24, P < .01], whereas the types of EGFR mutation did not affect survival (Figure 5 and Supplemental Figure 3), which was also observed in another recent study using propensity score matching [25].…”
Section: Discussionsupporting
confidence: 73%
“…Our findings provided further evidence that EGFR gene mutation varied by clinicopathological features which showed some predictors for EGFR gene mutation. So far, the results of survival difference between Del19 and L858R subtypes were still inconsistent 19. In our study, the survival time of exon 18 group was statistically lower than that of exon 19 group and exon 21 group, but the survival time between exon 19 group and exon 21 group was not statistically different, suggesting there were no differences in the survival time of Del19 and L858R subtypes in the patients with lung adenocarcinoma, which needed to be further investigated.…”
Section: Discussioncontrasting
confidence: 51%
“…Many groups have explored whether initial EGFR ‐activating mutation subtypes might serve as a prognostic factor for TKI treatment and possible TKI resistance with T790M mutation (Deng et al ., ; Ma et al ., ; Matsuo et al ., ; O'Kane et al ., ; Zhuo et al ., ). Recently, a meta‐analysis by Wu group suggested that tumors harboring EGFR 19del had a higher T790M mutation rate than those having L858R (Deng et al ., ).…”
Section: Discussionmentioning
confidence: 98%